The Effect of Income on Delinquency: Comment - Wveicher, John C. (American Economic Review, 2016)
In March 1966 issue of this Review, Belton Fleisher proposed an analytical framework for assessing relationship between income and juvenile delinquency and has attempted to measure effect of income on delinquency. In a series of multiple regression analyses, he finids a general pattern of behavior. . in which the overall effect of income on delinquency appears to be negative... although there is a partial off-setting effect as a result of positive influence of income on payoff for property crimes. He also finds that unemployment appears to be a cause of delinquent behavior... (p. 132), which is consistent with his previous work on subject. Fleisher's results, however, depend heavily on choice of variables used to represent tastes for delinquency. It is purpose of this comment to show that, at least for only set of published data used by Fleisher, which is also data regarded by him as niost useful for investigating delinquency (74 community areas within Chicago): a more accurate measure of one important taste concept is available, and its inclusion substantially alters Fleisher's results. Secondlv, Fleisher's economic variables are highly collinear with additionial variables, reflecting other aspects of taste for delinquency, which might reasona'bly be included in his regressions. XVhen these variables are added, Fleisher's results are further modified and his conclusions, particularlIy those with policy implications, are vitiated.